2015
DOI: 10.1136/annrheumdis-2015-eular.6265
|View full text |Cite
|
Sign up to set email alerts
|

FRI0258 A Novel MRI-Based Longitudinal Scoring System for Arterial Involvement in Large-Vessel Vasculitis

Abstract: BackgroundAlthough prevention of arterial progression is a hard therapeutic goal in large-vessel vasculitides (LVV), there is neither an agreed definition of progression nor a proposed method to globally assess arterial injury. This lack of validated clinimetry limits the feasibility of clinical trials. Although distinguishing disease activity from damage in Takayasu arteritis (TA) is difficult, current damage indices lack imaging data. Outside LVV, the only validated quantitative methods to assess arterial da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Turning to those with active disease at presentation, Kerr followed 34/60 patients angiographically, and 88% exhibited disease progression [29]. Our recent prospective longitudinal MR angiography study of unselected patients receiving treatment revealed that 40% of vasculitic lesions remained stable, 37% progressed and 23% improved (median 18 months) [33]. A recent study reported 10-year event-free survival, relapse-free survival and complication-free survival rates approaching 48, 70 and 54% respectively [31].…”
Section: Natural History Of Takmentioning
confidence: 98%
See 2 more Smart Citations
“…Turning to those with active disease at presentation, Kerr followed 34/60 patients angiographically, and 88% exhibited disease progression [29]. Our recent prospective longitudinal MR angiography study of unselected patients receiving treatment revealed that 40% of vasculitic lesions remained stable, 37% progressed and 23% improved (median 18 months) [33]. A recent study reported 10-year event-free survival, relapse-free survival and complication-free survival rates approaching 48, 70 and 54% respectively [31].…”
Section: Natural History Of Takmentioning
confidence: 98%
“…This approach requires a much shorter MRI acquisition time than detailed assessment of changes in the arterial wall. Furthermore, we have shown that monitoring in this way with MRI allows accurate assessment of disease extent and phenotype and long-term monitoring of disease evolution [33].…”
Section: Time-consumingmentioning
confidence: 99%
See 1 more Smart Citation